✔ 最佳答案
If T is a right triangle, and a ≤ b ≤ c, then
Case 1: if a is a hypotenuse, then
a ≠ b and a ≠ c as there is one, and only one hypotenuse in a right triangle, and
a is the greatest, hence
a > b and a > c, but this contradicts the assumption, so
a is not the hypotenuse.
Case 2: if b is a hypotenuse, then
b ≠ a and b ≠ c as there is one, and only one hypotenuse in a right triangle, and
b is the greatest, hence
b > a and b > c, but "b > c" contradicts the assumption, so
b is not the hypotenuse.
From case 1 and 2, c is the hypotenuse, and
a ≤ b < c.
Thus,
a^2 + b^2 = c^2 (Pythagorean Theorem)
(a^2 + b^2)^3 = (c^2)^3
a^6 + 3a^4b^2 + 3a^2b^4 + b^6 = c^6
3a^4b^2 + 3a^2b^4 = c^6 - a^6 - b^6
a^4b^2 + a^2b^4 = (c^6 - a^6 - b^6)/3
a^2b^2(a^2 + b^2) = (c^6 - a^6 - b^6)/3
(abc)^2 = (c^6 - a^6 - b^6)/3